Formulation and Evaluation of Micro Emulsion for the Treatment of Bacterial Meningitis - Bhonde G. Akash; Dr. Sandeep C. Atram; Mandwe S. Vrushabh; Bawankar V. Dipali; Puri G. Ashutosh (Asian Journal of Pharmaceutical Research and Development, 2025)
The aim of the present study was to prepare antibacterial drug loaded microemulsion. Antibactrial drug loaded Microemulsion were prepared by water titration method. The microemulsions were further characterized for particle size, zeta potential, pH, viscosity, drugcontent, and in vitro drug release behavior. The results revealed that this method is reproducible, more feasible and led to the entrapment of drug with an expected sustained release. The nanoparticle precipitated was with particle size of 176.8 nm, zeta potential of −29 mV, pH is determined in 4.5 to 6.5 and Viscouse in flow. The Drug content was noted was 83.95%. In vitro release was about 32.16% release in 1 h. When the regression coefficient values were compared, it was observed that ‘R2 ’ values of first order was maximum i.e. 0.9644 hence indicating drug release from formulation was found to follow zero order release kinetics. Antibactrial drug-loaded Microemulsion may be a good choice for the improvement of bioavailability and reduction in toxicity.